Retrospective exploratory dual-center analysis of temporary transvenous cardiac pacing in cardiogenic shock - Clemens Walter von Musil; Valentina Riederer; Leonhard Pilsbacher; Carina Maria Paulus; Severin Rudinger; Sophia Bodlee; Jonas Gmeiner; Julius Fischer; Julius Steffen; Sven Peterß; Stefan Kääb; Moritz Sinner; et al. (Scientific Reports)
Abstract Temporary transvenous cardiac pacing (TTP) is commonly used to manage hemodynamically compromising, drug-refractory brady- and tachyarrhythmias in the intensive care setting. Despite previous studies analyzing TTP treatment, data on its use in patients with cardiogenic shock (CS) remain limited. This retrospective exploratory analysis aimed to investigate the utilization of TTP in patients experiencing CS, with a particular focus on treatment characteristics, complication rates, predictive factors, and outcomes across different subgroups. We retrospectively included registry data from 184 patients who underwent TTP therapy from 1561 cases of CS treated at the Intensive Care Units (ICUs) of two university hospitals in Germany between 2010 and 2023. Bradycardia due to acute myocardial infarction was the primary indication for TTP implantation in patients with CS. The median duration of TTP therapy was 65 h, during which complications occurred in 12.0% of cases, 3.3% were classified as severe. We found that culprit lesions in the Right Coronary Artery (RCA) were more likely to necessitate TTP treatment in patients with acute myocardial infarction complicated by cardiogenic shock (AMI-CS) (OR 2.52, 95% CI 1.54–4.11, p < 0.001). In non-AMI-CS patients, age (OR 1.03, 95% CI 1.01–1.05, p < 0.005) and myocarditis (OR 3.21, 95% CI 1.19–8.64, p = 0.02) were associated with a higher incidence of TTP therapy during ICU treatment. Further studies are needed to validate these observations. Trial registration: LMUshock registry (WHO International Clinical Trials Registry Platform Number DRKS00015860).